2014
DOI: 10.1017/s136898001400055x
|View full text |Cite
|
Sign up to set email alerts
|

The iodized salt programme in Bangalore, India provides adequate iodine intakes in pregnant women and more-than-adequate iodine intakes in their children

Abstract: Objective: To compare the iodine status of pregnant women and their children who were sharing all meals in Bangalore, India. Design: A cross-sectional study evaluating demographic characteristics, household salt iodine concentration and salt usage patterns, urinary iodine concentrations (UIC) in women and children, and maternal thyroid volume (ultrasound). Setting: Antenatal clinic of an urban tertiary-care hospital, which serves a low-income population. Subjects: Healthy pregnant women in all trimesters, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…This higher crushed salt preference was also observed in our study. 12 Limitations which can be considered in our study include observer bias in inference of MBI kit results. Some household members predominantly involved in cooking were not involved in purchase of cooking salt and hence could lead to errors in data provided.…”
Section: Discussionmentioning
confidence: 96%
“…This higher crushed salt preference was also observed in our study. 12 Limitations which can be considered in our study include observer bias in inference of MBI kit results. Some household members predominantly involved in cooking were not involved in purchase of cooking salt and hence could lead to errors in data provided.…”
Section: Discussionmentioning
confidence: 96%
“…In their recent review, Yadav et al reported that 59.5-95% of pregnant women were consuming adequately iodized salt in India, 21 but the condition is skewed in rural and tribal communities. 22,23 While some studies indicate widespread iodine deficiency among pregnant women of India, 13,23,24 others report of adequacy. 12,25,26 While evaluating iodine adequacy among healthy women of the community, we observed an overall deficiency (117.94 mg/l).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported different results, with a higher median UIC in children than in pregnant women [20,21]. In these studies from Thailand and India [20,21], the children and pregnant women shared one or more meals, but the time and location of spot urine sampling may have differed. Moreover, the pattern of supplement intake was different compared to our Danish study.…”
Section: Methods To Evaluate Id In Pregnant Womenmentioning
confidence: 98%
“…3) [16]; however, iodine supplement use was much more frequent among pregnant women than among male partners and children [16]. Other investigators have reported different results, with a higher median UIC in children than in pregnant women [20,21]. In these studies from Thailand and India [20,21], the children and pregnant women shared one or more meals, but the time and location of spot urine sampling may have differed.…”
Section: Methods To Evaluate Id In Pregnant Womenmentioning
confidence: 99%